Nanoemulsion Increases the Antifungal Activity of Amphotericin B against Four Candida auris Clades: In Vitro and In Vivo Assays - Marena, Gabriel Davi [UNESP]; Ruiz-Gaitán, Alba; Garcia-Bustos, Victor; Tormo-Mas, María Ángeles; Pérez-Royo, Jose Manuel; López, Alejandro; Bernarbe, Patricia; Pérez Ruiz, María Dolores; Zaragoza Macian, Lara; Vicente Saez, Carmen; Avalos Mansilla, Antonia; Gómez, Eulogio Valentín; et al. (MDPI, 2023)
Candida auris is an emerging yeast of worldwide interest due to its antifungal resistance and mortality rates. The aim of this study was to analyse the in vitro and in vivo antifungal activity of a nanoemulsion loaded with amphotericin B (NEA) against planktonic cells and biofilm of C. auris clinical isolates belonging to four different clades. In vivo assays were performed using the Galleria mellonella model to analyse antifungal activity and histopathological changes. The in vitro results showed that NEA exhibited better antifungal activity than free amphotericin B (AmB) in both planktonic and sessile cells, with >31% inhibition of mature biofilm. In the in vivo assays, NEA demonstrated superior antifungal activity in both haemolymph and tissue. NEA reduced the fungal load in the haemolymph more rapidly and with more activity in the first 24 h after infection. The histological analysis of infected larvae revealed clusters of yeast, immune cells, melanisation, and granulomas. In conclusion, NEA significantly improved the in vitro and in vivo antifungal activity of AmB and could be considered a promising therapy for C. auris infections.
Keywords: amphotericin B; Candida auris; Galleria mellonella; infectious disease; nanoemulsion